Mechanistic Insights on Concentrated Lithium Salt/Nitroalkane Electrolyte Based on Analogy with Fluorinated Alcohols. Issue 5 (27th January 2020) - Shida, Naoki; Imada, Yasushi; Okada, Yohei; Chiba, Kazuhiro
Abstract : Fluorinated alcohols such as 1, 1, 1, 3, 3, 3‐hexafluoro2‐propanol (HFIP) and 2, 2, 2‐trifluoroethanol (TFE) have emerged as powerful solvents in oxidation chemistry including hole catalysis. In this paper, we describe the similarity of lithium salt/nitroalkane electrolytes with fluorinated alcohols in electrosynthesis. Based on the results from electrosynthesis, Raman and nuclear magnetic resonance spectroscopy and cyclic voltammetry (CV), we have demonstrated that the combination of lithium cation, perchlorate or sulfonimide anions, and nitroalkanes make up an ideal solution to stabilize radical cations, just like fluorinated alcohols. The CV results suggested that the radical cation of 1, 4‐dimethoxybenzene is better stabilized in 1.0 m LiClO4 than in a neat HFIP solution. A mechanistic proposal for this electrolyte system described herein will give new directions for designing reaction systems for a wide range of oxidation chemistries. Abstract : Fluorinated alcohols are unique solvents in oxidation chemistry due to their ability to stabilize radical cations. The combination of lithium cations, perchlorate or sulfonimide anions, and nitroalkanes is an ideal solution for stabilizing radical cations, just like fluorinated alcohols. The reaction was evaluated by Raman and NMR spectroscopy and cyclic voltammetric measurements.